EFFECTIVE METHODS FOR DEVELOPING LOGICAL THINKING IN PRIMARY SCHOOL MATHEMATICS LESSONS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines effective methods for developing logical thinking in primary school mathematics lessons within the context of contemporary pedagogical education. Logical thinking is interpreted as an essential component of pupils’ cognitive development, enabling them to analyze, compare, generalize, classify, justify, and solve mathematical problems consciously and consistently. The study focuses on such instructional methods as problem-based learning, didactic games, comparison and classification tasks, mathematical discussions, visual modeling, heuristic questions, and differentiated exercises adapted to pupils’ age and learning abilities. Particular attention is given to the role of the teacher in organizing an interactive learning environment in which pupils are encouraged to reason, explain their answers, identify patterns, and construct simple conclusions independently. The article argues that the systematic integration of logically oriented tasks into mathematics lessons contributes not only to stronger subject achievement, but also to the formation of intellectual independence, accuracy of thought, and sustained interest in learning. It is concluded that effective development of logical thinking in primary mathematics depends on methodological consistency, age-appropriate task design, and the purposeful combination of traditional and innovative teaching strategies in the educational process.
Keywords: Logical thinking, primary education, mathematics lessons, problem-based learning, didactic games, cognitive development, mathematical reasoning, interactive methods, heuristic tasks, pedagogical effectiveness.